2021
DOI: 10.1016/j.ecolmodel.2020.109378
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic role of grasslands as sources of soil-dwelling insect pests: New insights from in silico experiments for pest management strategies

Abstract: Highlights: The role of grassland in field colonisation by insect pests is investigated in silico  Population dynamics of wireworms is modelled, accounting for life cycle and dispersion  Spatiotemporal effects of grassland in field history, field neighbourhood or their interaction, depend on the pest life cycle and its dispersal capacity  Grassy areas can act either as pseudo-sinks or as sources on neighbouring crops  Control strategies based on grassland arrangements appear trait-specific

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Insect pests are almost a year-round problem in the whole universe. Pests can be above ground or below ground [23]. While it is somewhat easier to observe foliar insects, it is a daunting task to really know what is inside the soil before it is too late.…”
Section: Soil Insect Pestsmentioning
confidence: 99%
“…Insect pests are almost a year-round problem in the whole universe. Pests can be above ground or below ground [23]. While it is somewhat easier to observe foliar insects, it is a daunting task to really know what is inside the soil before it is too late.…”
Section: Soil Insect Pestsmentioning
confidence: 99%
“…It is commonly stated that grasslands, as well as uncropped field margins and areas, provide the most favorable habitat for egg-laying and larval development [10,32], and may act as reservoirs from which larvae and click beetles disperse into adjacent crops [33,34]. Field history, plus landscape context through its effect on click beetle dispersal, may shape the pest abundance at the field scale.…”
Section: Risk Factorsmentioning
confidence: 99%
“…More generally, while landscape context has been identified as a risk factor (Section 2.1), habitat manipulation remains underused. In their theoretical study, Poggi et al [34] addressed the role of grassland in the field history, field neighborhood, and both. They have shown that species with a short life cycle are highly responsive to changes in land use, and that the neighborhood effect strongly relies on assumed dispersal mechanisms (random vs, directed movements).…”
Section: Habitat Manipulationmentioning
confidence: 99%